ANALISIS TEMUAN PENELITIAN TENTANG PEMBELAJARAN KONTEKSTUAL BERBASIS KEARIFAN LOKAL PADA MATERI IPAS DI SEKOLAH DASAR: SYSTEMATIC LITERATURE REVIEW - Nita Khusnun Nandifa; Eko Handoyo; Hanafi Hussin; Indriana Eko Armadi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study analyzes research findings on the implementation of Contextual Teaching and Learning (CTL) based on local wisdom in elementary school IPAS learning. The study addresses the limited integration of cultural context in classroom practices, which reduces the relevance and effectiveness of learning. The objective is to synthesize empirical evidence related to learning outcomes and cultural awareness. This research applies a Systematic Literature Review (SLR) using the PRISMA approach. The initial search identified 500 articles, which were systematically screened and reduced to 20 eligible studies based on predetermined inclusion criteria. The findings indicate that local wisdom-based CTL consistently improves cognitive learning outcomes, student engagement, and cultural awareness. Most studies show a positive trend in strengthening both cognitive and affective domains. The integration of real-life cultural contexts makes learning more meaningful, relevant, and closely connected to students’ experiences. These results confirm that contextual learning based on local wisdom is effective in supporting IPAS learning in elementary schools. Future research is recommended to examine its implementation across diverse educational contexts and to develop adaptive learning models based on local characteristics.